(untitled) (Italian Journal of Public Health, 2009)
Abraham Flexner lit the fire that freed American doctors from obsolete aspects of their training. Edmund Pellegrino was the prudent fireman who acknowledged the risk of too broad a fire and put in place safe guards to protect those aspects that needed to be saved. The prodigious leap forward in medicine due to the “laboratory centred” training introduced by Flexner’s proposals for medical training began to have negative effects in daily medical practice, particularly with regards to the increasing technological input in medicine and the perception that there was a lack of sensitivity to the humanistic aspects of health. It took a strong and genial personality, no less than Abraham Flexner, to correct the course of medical training in the USA and to restore the balance between these two dimensions.